Lack of family planning: The highlighted burden - Munira Minaz Ali; Alizah Alaman (International Journal on Women Empowerment, 2016)
Family planning is defined as a practice through which number of children and the intervals between their births can be controlled. The need of using contraceptives cannot be neglected in Pakistan, as this would result in unwanted pregnancies and un-safe abortions. Illiteracy, lack of knowledge, fear of side effects, and other socio-cultural factors create obstacles in using family planning methods. These obstacles in turn create adverse impacts on women health and society. For instance, failure to use contraceptives can cause unintended pregnancies which would leave the women at the risk of pregnancy related complications resulting in maternal morbidity and mortality. Moreover, multiple pregnancies also cause financial and social distress resulting in lack of ability to fulfill basic needs of a child. Thus, important measures need to be taken to alleviate the precipitating factors and to improve maternal and child health.